The host [videorecording (DVD)] - Niccol, Andrew; Ronan, Saoirse, 1994-; Abel, Jake, 1987-; Irons, Max, 1985-; Meyer, Stephenie, 1973- (Universal Studios Home Entertainment, 2013)
When an unseen enemy threatens mankind by taking over humans' bodies and erasing their minds, a young woman risks everything to protect the people she cares about most.